Throughput Estimation with Regard to Airtime Consumption Unfairness in Mixed Data Rate Wi-Fi Networks - Abdul-Hadi, Alaa Mohammed; Tarasyuk, Olga; Gorbenko, Anatoliy; Kharchenko, Vyacheslav; Hollstein, Thomas (Communications - Scientific letters of the University of Zilina, 2014)
The paper discusses throughput unfairness inherent in the very nature of mixed data rate Wi-Fi networks employing random media access control technique CSMA/CA. This unfairness exhibits itself through the fact that slow clients consume more airtime to transfer a given amount of data, leaving less airtime for other clients. This decreases the overall network throughput and significantly degrades performance of high data rate clients. In the paper we propose mathematical models considering airtime unfairness and estimating wireless networks throughput depending on number of network connections and their data rates. These models show that all wireless clients have an equal throughput independently of data rates used by them. We verify our theoretical findings by running natural experiment and show that client’s throughput approximates to the data rate of the slowest client.